Motherhood and the late nineteenth-century Irish workhouse - Bolger, Judy (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2025)
This thesis explores the experiences of impoverished mothers in late nineteenth-century Ireland through their interaction with the Irish poor law system, offering a new perspective on welfare, gender, and institutional care. Building on the seminal work of historians such as Virginia Crossman, this study moves beyond administrative histories of the Irish Poor Law to consider how women negotiated maternity within and around the workhouse. It adopts a life-cycle approach to trace women's lives through pregnancy, childbirth, and early motherhood, using a micro-historical methodology to uncover individual strategies, voices, and decisions. Methodologically, this thesis draws on a wide range of local poor law records, including workhouse indoor registers and board of guardians' minute books. Other material, such as the Vice-Regal Commission on Poor Reform (1906) and a vast collection of newspapers, are used to investigate women's interactions with the workhouse. Alongside this, civil birth, marriage, and death records, and census data are used to trace women's maternal lives. This approach allows for a close reading of women's lives and a broader analysis of the welfare practice. This thesis reveals the gendered nature of relief, particularly in the case of unmarried mothers. It shows how women navigated complex welfare landscapes, engaged with poor law officials, asserted claims to maintenance, and made difficult choices about infant care. While the workhouse could offer material support during a crisis, it was also a site of regulation, discipline, and emotional strain. Ultimately, this study recasts the workhouse as a contested site of maternal care and agency. It brings a new maternal lens to the history of Irish welfare, illuminating how policy and poverty shaped women's reproductive lives under the late nineteenth-century Irish Poor Law.
APPROVED
Keywords: Motherhood; Gender; Poverty; Pregnancy; Childbirth; Breastfeeding; Welfare